A Praça da Matriz: histórias, memórias e experiências de uma intervenção urbana em Itapecirica da Serra - São Paulo 1980-2003 - Santos, Patrícia Cerqueira dos (2006)
This master s thesis sews together a reflection about the city of Itapecerica da Serra, São Paulo, from 1980 to 2003. An urban intervention of significant impact, the reform of the Central Plaza became the theme for the development of this research project. The memories and histories recounted in interviews with residents, users, passers-by, and the city s public sector representatives, interwoven with other documents both written and figurative, reveal the varied meanings the plaza, symbol of the city, has had on their lives as well as on that of the city itself. Fundamental to this study are the effects of this intervention on the way of knowing and living with the plaza as a space. The analysis of these memories challenge some facets of the history that commonly travels around the city and reveal other possibilities for comprehending the construction of local history. The thesis follows chronological order. The first part narrates and analyzes the history of the city and the slow process of formation of the Central Plaza. The second part follows a chronology shaped by the memories of users to examine different moments of the intervention, analyzing the impact of these changes on the daily use and experience of the plaza. The third part examines the contradictions between the revitalization project and disputes in the city related to its realization